Analisis Higiene Sanitasi Pedagang, Kandungan Rhodamin B, dan Escherichia coli pada Produk Terasi: Studi di Pasar Tanjung, Jember - Rachmah, Luthfiyyah; Ellyke, Ellyke (Pustaka Kesehatan, 2024)
Terasi is a food made from shrimp or rebon and then processed by fermentation. This processed food must keep the quality of food safe and apply good sanitation and hygiene from the beginning of production to the hands of consumers. This study used descriptive quantitative with descriptive observation method. The sample in the study used a total sampling technique consisting of 15 traders and terasi. The variables in this study were personal hygiene, terasi storage, serving terasi, Rhodamine B contains, and total bacteria of E.coli. The results showed that the personal hygiene of terasi traders at Tanjung Market, Jember Regency was in the sufficient category (53%) and as many as (47%) were in the good category. Most of the terasi storage (80%) are qualified. Most of the serving of terasi (93%) are qualified. The result is Rhodamine B was found in 5 terasi samples also there is E.coli in 2 terasi samples.